Properti psikometris Big Five Inventory–2 versi Indonesia - Firdhan Achmadan; Edo Sebastian Jaya; Sali Rahadi Asih (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2022)
The five personality traits are currently seen as the most widely used theoretical framework in explaining the variability of human behavior. Big Five Inventory (BFI) is one of the well-known inventories that contributes to the progress of the big five research. Recently, the developer updated and published the Big Five Inventory-2 (BFI-2). Various studies have been conducted to expand the scope of validation, but until now the testing has not been carried out involving Indonesian participants. The purpose of this study was to evaluate the psychometric properties of the BFI-2 in the Indonesian version. The researcher corresponds with the developer to obtain BFI-2 which has been officially translated by the International Situations Project (ISP). Data were collected by distributing online surveys through various social media platforms. A total of 1061 participants were involved in this study. The result showed adequate internal consistency on the domain level and somewhat lower on the facet level. The BFI-2 domains and facets also showed good convergent-discriminant validity in relation to IPIP-BFM-50 and TIPI. The factor analysis shows that the model fits the data after seven problematic items were not included in the analysis. Therefore, we concluded that the questionnaire could be used to measure the Big Five personality traits in Indonesia provided the problematic items found to be invalid are deleted.